Analysis of the Deixis in Spider-Man: No Way Home Movie - Ni Made Dhyana Satwika Putri,; Putu Ayu Asty Senja Pratiwi,; A.A.Sg. Shanti Sari Dewi, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze deixis applied in Spider-Man: No Way Home movie and its reference by using the theory of deixis by Levinson (1983) and theory of role of context by Dijk. This study applies descriptive qualitative research method in analyzing deixis and its reference applied in Spider-Man: No Way Home movie script. The procedures are: collecting data with observation method and documentation technique. This study applies the theory of deixis by Levinson (1983) and Dijk. In data analysis and presented descriptively by informal method. The finding shows that all types of deixis are applied in the data source with the quantity of 920 in total; person deixis: 692 data, spatial deixis: 28 data, temporal deixis: 18 data, social deixis: 14 data, and discourse deixis: 168 data. Person deixis consist of first-person deixis to identify the speaker, second person deixis used to appoint the addressee, and third person deixis refer to a person neither the speaker nor the addressee. Spatial deixis used to explain the location of certain utterance. Temporal deixis described an exact time of utterance. Social deixis illustrated certain relationships among characters. Lastly, discourse deixis functioned to refer to something that being talked about in the same utterance.